Bank liquidity, the maturity ladder, and regulation - de Haan, Leo; van den End, Jan Willem (Journal of banking & finance, 2013)
•We investigate liquidity behaviour of banks subject to Basel III-type regulation.•We relate banks’ liquidity to the full maturity ladder of future cash flows.•Most banks hold more liquid assets than required by regulation.•Banks consider cash flows beyond 1month when setting liquid asset holdings.•More solvent banks hold fewer liquid assets against liquid liabilities. We investigate the liquidity management of 62 Dutch banks between January 2004 and March 2010, when these banks were subject to a liquidity regulation that is very similar to Basel III’s Liquidity Coverage Ratio (LCR). We find that most banks hold more liquid assets against their stock of liquid liabilities, such as demand deposits, than strictly required under the regulation. More solvent banks hold fewer liquid assets against their stock of liquid liabilities, suggesting an interaction between capital and liquidity buffers. However, this interaction turns out to be weaker during a crisis. Although not required, some banks consider cash flows scheduled beyond 1month ahead when setting liquidity asset holdings, but they seldom look further ahead than 1year.